1998
DOI: 10.1111/j.1440-1819.1998.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Social support and pregnancy:I. Factorial structure and psychosocial correlates of perceived social support

Abstract: In a questionnaire survey among 1329 first‐trimester pregnant women, social support providers were divided by factor analysis into husband, ‘premarital network’ (parents and friends) and ‘postmarital network’ (children and mother‐in‐law), while social support contents were divided into ‘given’ (emotional, informational and instrumental support) and ‘giving’ (nurturing opportunity and general confiding). The husband was most frequently nominated by the woman as the support provider in both of these categories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A partner is the most important person as a resource of "perceived" social support in the perinatal period in Japan (Kitamura, Toda, Shima, Sugawara, & Sugawara, 1998). Compared with Western countries, the self-construal in Japanese people becomes most meaningful and complete when it is cast in the appropriate social relationship (Markus & Kitayama, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A partner is the most important person as a resource of "perceived" social support in the perinatal period in Japan (Kitamura, Toda, Shima, Sugawara, & Sugawara, 1998). Compared with Western countries, the self-construal in Japanese people becomes most meaningful and complete when it is cast in the appropriate social relationship (Markus & Kitayama, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of social support prevents postpartum depression (Dennis & Ross, 2006;Corrigan, Kwasky, & Groh, 2015). During the perinatal period, most women listed their partners as the most reliable person whom they sought for social support (Kitamura, Toda, Shima, Sugawara, & Sugawara, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have argued that providing social support to primipara women in both the pre-and postnatal period must be prioritized by health-care providers because of evidence that social support can ensure a successful transition into motherhood (Logsdson & Davis, 2003;Wilkins, 2006). Moreover, a mother's evaluation of her birthing experience is directly linked with the quality, origin, and extent of support acquired from her health-care professional as well as her partner (Simon, Johnson, & Liddell, 2016). Low levels of social support have been associated with higher rates of postnatal depression, especially in the 6 weeks following giving birth (Leahy-Warren, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kitamura et al studied over 1000 pregnant women and found that their perception of nurturing opportunities, an aspect of perceived support, was correlated with older age and more children. 13 The quality and quantity of support received in the course of past events may determine an individual’s satisfaction with current interpersonal relationships. Confidence and contentment in social relationships may date back to childhood; childhood experiences and parental behavior towards the subject may influence the later cognitive style.…”
Section: Introductionmentioning
confidence: 99%